EVALUATION Of QUALITY CONTROL FOR THE END OF PRODUCT IN “UD NANANG” BRICK COMPANY YOGYAKARTA - Dona, Evi; Lastari, SE.,MM, Siwi (Management, 2010)
The purpose of this study was to determine whether the product is damaged in